Pengaruh Kompetensi, Kepuasan Kerja, dan Komitmen Terhadap Kinerja Guru SMK Negeri 1 Binjai - Putri, Dwi Ananda; Insan, Muhammad Yalzamul; Setiawan, Nashrudin (Indo-MathEdu Intellectuals Journal, 2025)
This study aims to analyze the influence of competence, job satisfaction, and commitment on teacher performance at SMK Negeri 1 Binjai. The research uses a quantitative approach with an associative method. Primary data was collected through the distribution of questionnaires to 72 respondents. The data analysis technique uses multiple linear regression with the help of SmartPLS 4 software. The results of the analysis showed that competence had a positive and significant effect on teacher performance (t-statistic = 2.935 > 1.99; p = 0.000 < 0.05). Job satisfaction also had a positive and significant effect on teacher performance (t-statistic = 2.916 > 1.99; p = 0.000 < 0.05). In addition, commitment had a positive and significant influence on teacher performance (t-statistic = 4.628 > 1.99; p = 0.000 < 0.05). Thus, the three independent variables significantly affect the performance of teachers at SMK Negeri 1 Binjai.